Acne: An Ignored Dermal Malady (Asian Journal of Pharmaceutics (AJP), 2022)
Acne vulgaris is a dermal inflammatory condition that originates as a result of clogging of the pilosebaceous unitand is a complicated skin ailment that affects over 85% of young people around the world. The disorder has acrucial impact on a patient’s life quality. The causative bacterium for acne is Propionibacterium acne. The articleemphasizes on the prime factors responsible for the occurrence of acne and also highlights the various forms ofacne, types of scars and clinical diagnosis for the same. Various options for the management of acne includingtopical agents, oral antibiotics, and therapies along with preventive methods are discussed in the article.